2022
DOI: 10.3390/biom12070934
|View full text |Cite
|
Sign up to set email alerts
|

Major Adverse Cardiovascular Events and Mortality Prediction by Circulating GDF-15 in Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis

Abstract: Background: Growth differentiation factor 15 (GDF-15) is a homeostatic cytokine that regulates neural and cardio-metabolic functions, and its release is increased in response to stress, injury, and inflammation. In patients with coronary artery disease and heart failure (HF), three separate meta-analyses have found that elevated circulating GDF-15 was predictive of major adverse cardiovascular events (MACE), but none has evaluated its effects on incident MACE including HF and mortality hazard in type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis revealed that GDF-15 consistently adds prognostic information for myocardial infarction and stroke, CV death, and heart failure beyond clinical risk factors and cardiac biomarkers of CVDs [77]. The prognostic significance of elevated circulating GDF-15 levels has also been demonstrated for T2DM [78]. However, it remains unclear whether the effects of GDF-15 in MetS are causative or whether its levels are a consequence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis revealed that GDF-15 consistently adds prognostic information for myocardial infarction and stroke, CV death, and heart failure beyond clinical risk factors and cardiac biomarkers of CVDs [77]. The prognostic significance of elevated circulating GDF-15 levels has also been demonstrated for T2DM [78]. However, it remains unclear whether the effects of GDF-15 in MetS are causative or whether its levels are a consequence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…GDF-15 has been applied as a biomarker for predicting the risk of cardiovascular diseases and cardiovascular events (Adela and Banerjee, 2015;Havranek and Marek, 2021;May et al, 2021;Pence, 2022;Xie et al, 2022;Sawalha et al, 2023). For instance, GDF-15 is upregulated in patients with coronary artery disease (CAD) compared to non-CAD controls, yielding a diagnostic value with an AUC of 0.9 for CAD (Hassanzadeh Daloee et al, 2021); moreover, GDF-15 is greater in heart failure patients with ischemic heart disease than in controls without ischemic heart disease (Elsewify et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, GDF-15 is upregulated in patients with coronary artery disease (CAD) compared to non-CAD controls, yielding a diagnostic value with an AUC of 0.9 for CAD (Hassanzadeh Daloee et al, 2021); moreover, GDF-15 is greater in heart failure patients with ischemic heart disease than in controls without ischemic heart disease (Elsewify et al, 2022). In addition, GDF-15 predicts the risk of major adverse cardiovascular events in patients with diabetes, as reported by a meta-analysis involving nearly twenty thousand patients (Xie et al, 2022). Furthermore, a very interesting metaanalysis reports that GDF-15 is consistently useful for prognostic prediction of the risk of cardiovascular death and hospitalization for heart failure among different types of atherosclerotic cardiovascular diseases (Kato et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarkers such as GDF-15 have been proposed as a specific biomarker of bleeding are limited by their lack of specificity, being also predictive of non-bleeding outcomes, including all-cause death and cardiovascular death, as well as major adverse cardiac events and the progression of chronic kidney disease (9)(10)(11)(12). Indeed, the biomarker-based ABC-bleeding and ABC-stroke scores demonstrated similar predictive ability for outcomes beyond stroke and bleeding, including myocardial infarction, acute heart failure, a composite of cardiovascular events, and all-cause deaths (13).…”
mentioning
confidence: 99%